SOCIAL ENTREPRENEURSHIP IN SUSTAINABLE DEVELOPMENT: STRENGTHENING THE ENVIRONMENTAL PERSPECTIVE - Rezky, Muhammad Iqbal; Rasto, Rasto (Journal of Environmental Science and Sustainable Development, 2024)
Social entrepreneurship and sustainable development are closely related concepts. Social entrepreneurship applies entrepreneurial attributes with a focus on solving major social issues. The relationship between the two demonstrates the contribution of social entrepreneurship in addressing social and environmental problems, reducing poverty, and fostering sustainable economic growth. This research employs a bibliometric approach to analyze trends and patterns in 181 relevant articles published between 2015 and 2023. Findings indicate significant growth in research between 2019 and 2021. Countries and institutions such as Spain, the United States, and Universitat de Valencia stand out in these publications. The bibliometric analysis also reveals influential journals like Sustainability and the Journal of Cleaner Production. Key terms such as 'sustainable development,' 'social entrepreneurship,' and 'sustainability' highlight five thematic clusters encompassing economic development, the role of social entrepreneurship in corporate social responsibility, rural community development, and the contribution of social entrepreneurship to the United Nations (UN) Sustainable Development Goals (SDGs). The research findings help in identifying future research directions and enhancing knowledge of social entrepreneurship's function in sustainable development. Leveraging these insights can empower social entrepreneurs to create a fairer, more sustainable future. In conclusion, further research could delve deeper into thematic clusters and consider regional influences to maximize their impact on the world.